Beyond the Joá: infrastructures and urban expansion towards Barra da Tijuca - Agueda, Rodrigo (2022)
During the 1960s and 1970s, the city of Rio deJaneiro was expanding towards the recentlyprojected neighborhood of Barra da Tijuca.The massive construction of Elevado do Joá’s infrastructural complex emerged as a key element of that expansion, connecting the South and the West zones of the city. This article aims to analyze how this construction served as a foundation not only for the expansion of the real estate market, but also for the creation of social imaginaries and new urban forms. Through newspaper articles from that time, I associate Joá’s construction with a new model of urban life that was rising in the modernist neighborhood of Barra da Tijuca.